Back to the basics: usefulness of naturally aged mouse models and immunohistochemical and quantitative morphologic methods in studying mechanisms of lung aging and associated diseases - Jaramillo Rangel, Gilberto; Chávez Briones, María de Lourdes; Ancer Arellano, Adriana Guadalupe; Miranda Maldonado, Ivett C.; Ortega Martínez, Marta Graciela (Multidisciplinary Digital Publishing Institute, 2023)
Aging-related molecular and cellular alterations in the lung contribute to an increased susceptibility of the elderly to devastating diseases. Although the study of the aging process in the lung may benefit from the use of genetically modified mouse models and omics techniques, these approaches are still not available to most researchers and produce complex results. In this article, we review works that used naturally aged mouse models, together with immunohistochemistry (IHC) and quantitative morphologic (QM) methods in the study of the mechanisms of the aging process in the lung and its most commonly associated disorders: cancer, chronic obstructive pulmonary disease (COPD), and infectious diseases. The advantage of using naturally aged mice is that they present characteristics similar to those observed in human aging. The advantage of using IHC and QM methods lies in their simplicity, economic accessibility, and easy interpretation, in addition to the fact that they provide extremely important information. The study of the aging process in the lung and its associated diseases could allow the design of appropriate therapeutic strategies, which is extremely important considering that life expectancy and the number of elderly people continue to increase considerably worldwide.